Administrative organization and its impact on achieving institutional excellence: An Applied Study on Abdul Latif Jameel Company - Al-Harithi, Badr Mohammed (Journal of Economic, Administrative and Legal Sciences, 2024)
The study aims to institutional excellence and how to achieve it and clarifying several models of administrative organization. The study assumed a statistically significant relationship between administrative organization and institutional excellence. And that there is a relationship of statistical significance between the lack of proper planning and the achievement of institutional excellence and the study used the method of stylistic analysis followed by SPSS using to validate the hypotheses of the study and the discussion and calculate the truthfulness of the internal consistency of the dimensions of the scale for dialogue as well as (SPSS) by using the One Way ANOVA test on a random sample of (50) employees of Abdul Latif Jameel Company in Jeddah. The study concluded that there is no statistically significant relationship between the organization Administrative and institutional excellence and there is a relationship of statistical significance between the lack of proper planning and the achievement of institutional excellence. The study also recommended the need to involve all employees of Abdul Latif Jameel Company in training courses for the use of computers in their work.
Keywords: organization; administrative organization; institutional excellence; Abdul Latif Jameel